2021
DOI: 10.1001/jamanetworkopen.2020.36344
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Clinical Decision Support on Diagnostic Imaging for Pediatric Appendicitis

Abstract: Key Points Question Can an electronic health record–linked clinical decision support tool reduce the use of diagnostic imaging in children and adolescents with emergency department visits for acute abdominal pain? Findings In this cluster randomized trial of 17 emergency departments caring for 5940 patients, the clinical decision support tool did not lead to an overall reduction in the use of computed tomography or ultrasonography. In 1 health care system, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…A recently published randomized trial to reduce imaging in children with abdominal pain across 17 EDs encountered similar provider reluctance to discharge patients home without imaging. 22 To address this concern, it is vital to remove the stigma associated with a patient returning to the ED with appendicitis who was previously seen and discharged home with return precautions. This is an acceptable outcome, as the diagnosis can be difficult to make when patients present soon after symptoms begin.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published randomized trial to reduce imaging in children with abdominal pain across 17 EDs encountered similar provider reluctance to discharge patients home without imaging. 22 To address this concern, it is vital to remove the stigma associated with a patient returning to the ED with appendicitis who was previously seen and discharged home with return precautions. This is an acceptable outcome, as the diagnosis can be difficult to make when patients present soon after symptoms begin.…”
Section: Discussionmentioning
confidence: 99%
“…A recent cluster randomized trial also demonstrated that an EHR integrated clinical decision support aid that utilized the pediatric appendicitis risk score led to a decrease in CT and ultrasound use among patients with low risk of appendicitis. 21…”
Section: Discussionmentioning
confidence: 99%
“…A recent cluster randomized trial demonstrated that an electronic medical record-linked clinical decision support tool that utilized the pARC score led to a decrease in CT and US use among patients with a pARC <15% in one healthcare system, with no safety concerns or adverse events. 23 Previous studies have shown favorable outcomes when selective imaging is used in patients with an intermediate risk of appendicitis. [24][25][26][27] In a prospective, observational cohort study conducted by Saucier et al at an academic pediatric ED, 119 (60%) of enrolled patients were found to be intermediate risk for appendicitis (PAS 4-7).…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy is most likely due to our small sample size; however, the rates of appendicitis are similar in these low‐risk categories, demonstrating the reproducibility of the pARC score in identifying low‐risk patients. A recent cluster randomized trial demonstrated that an electronic medical record‐linked clinical decision support tool that utilized the pARC score led to a decrease in CT and US use among patients with a pARC <15% in one healthcare system, with no safety concerns or adverse events 23 …”
Section: Discussionmentioning
confidence: 99%